2015
DOI: 10.1186/s13568-015-0126-3
|View full text |Cite
|
Sign up to set email alerts
|

Selenocystamine improves protein accumulation in chloroplasts of eukaryotic green algae

Abstract: Eukaryotic green algae have become an increasingly popular platform for recombinant proteins production. In particular, Chlamydomonas reinhardtii, has garnered increased attention for having the necessary biochemical machinery to produce vaccines, human antibodies and next generation cancer targeting immunotoxins. While it has been shown that chloroplasts contain chaperones, peptidyl prolylisomerases and protein disulfide isomerases that facilitate these complex proteins folding and assembly, little has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…This mutation blocks the trans -splicing of psaA-exon1 mRNA and has been shown to greatly increase expression of transgenes fused to the psaA promoter/5′UTR (Michelet et al 2011 ). Additionally, Ferreira-Camargo et al ( 2015 ) have reported that the inclusion of selenocystamine in the growth medium improves the accumulation of proteins containing disulfide bonds and could therefore also increase hGH yield.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation blocks the trans -splicing of psaA-exon1 mRNA and has been shown to greatly increase expression of transgenes fused to the psaA promoter/5′UTR (Michelet et al 2011 ). Additionally, Ferreira-Camargo et al ( 2015 ) have reported that the inclusion of selenocystamine in the growth medium improves the accumulation of proteins containing disulfide bonds and could therefore also increase hGH yield.…”
Section: Discussionmentioning
confidence: 99%
“…A new nuclear transformation method by microparticle bombardment was developed in Phaeodactylum tricornutum using PCR-amplified DNA fragments [ 83 ]. In addition, Ferreira-Camargo et al found that selenocystamine can improve accumulation of disulfide bonds-contained proteins in green algal chloroplasts [ 84 ].…”
Section: Brief Introduction To Microalgaementioning
confidence: 99%
“…More recently, selenocystamine improved the accumulation of disulfide containing proteins in chloroplasts of eukaryotic green algae. 13 Selenium is a particularly effective electrophile and nucleophile in nucleophilic exchange reactions, 14,15 due to its greater polarizability in comparison to sulfur and the lower pK a for selenol side-chain of Sec compared to thiol of Cys (5.2 versus 8.5, respectively). 16 Owing to the rapid oxidation of selenols by atmospheric oxygen, catalytic amounts of diselenides can be used for protein refolding under aerobic conditions.…”
mentioning
confidence: 99%
“…Acetonide 5 deprotection was achieved by TFA, providing diselenide 1 in quantitative crude yield. The product was purified via C 18 preparative reversed-phase (RP) HPLC and characterized by 1 H-, 13 C-and 77 Se-NMR and ESI-MS (see ESI †).…”
mentioning
confidence: 99%